PENGEMBANGAN HANDOUT BERBASIS MODEL SAINS TEKNOLOGI MASYARAKAT PADA MATERI WUJUD ZAT DAN PERUBAHAN ZAT UNTUK PEMBELAJARAN IPA FISIKA SMP KELAS VII SEMESTER 1 - Ayda Silfi Yana (Universitas Negeri Padang, 2014)
Handout based on the model STM (Science Technology Society) can facilitate students to understand the physics material and apply the concept of physics in everyday life. The general objective of this research is to produce handout based on the model STM (Science Technology Society) is a valid, practical and effective for substance and phase change topic in grade VII junior high school. The research conducted is a Research and Development (R & D). Data collection instruments were: sheet of validation experts, practicality test sheet by physics teacher, practicality test sheets by students, and the test results in cognitive domain. The results of research are: 1) a valid handout based on the model STM (Science Technology Society) with validity value about 89,59; 2) practicality handout by teacher value about 89,6; 3) practicality handout by student responses value about 88,5 and 4) handout is effective to improve learning physics of outcome of students